HP2: The Design of a 3D-Printed Partition for the Healthcare Environment - Kelly, Brian M. (ARCC Conference Repository, 2013)
As of 2012, the methods in which the construction industry fabricates a non-load bearing partition are virtually the same as 100 years ago. This process and assembly is perpetuated by a construction culture that thrives on convention. Sheet building materials are nominally controlled, assembly definitions are outlined through building codes, and trades continue a system of apprenticeship where techniques are passed down through generations. This is further complicated with a construction process that is the mediator between the conception of the designer and the built artifact. The aim of this research was to reconceive the conventional construction techniques of the partition in high performance, technology specific locations; an area that begs for development within a contemporary fabrication environment where new CNC technologies are able to translate mass-customized form into full scale, built assemblies. HP2 was a design research project into the potential of a fully digitally fabricated, high performance interior partition placed within the healthcare environment. Initial research indicated areas where design could assist in more effective delivery of healthcare. For example, altering the ways healthcare providers enter and exit the room, as well as the way air is moved through the room could better protect patients in these facilities. Additionally, research aimed to integrate the inclusion of digital form generation and fabrication techniques to consider the partition of tomorrow – one that allows synergy between the form, space, and various building systems. The design process investigated areas of acute care patient rooms, structural surfaces, architectural wall infill (poche), narrow spectrum sanitary lighting, adjustable and variable perforation, and patient room air ventilation. This process culminated in the manifestation of a 3d printed scale mockup of the partition with all systems present. Current projections of this project speculate on the potential of large scale 3D printing as a means to establish better connections between the high technology systems being requested and a fabrication technique which is supportive of that endeavor.